A copper-based metal–organic framework/graphene nanocomposite for the sensitive and stable electrochemical detection of DNA bases. Issue 5 (28th January 2020) - Wang, Xiuyun; Zhang, Jie; Wei, Yuanan; Xing, Tianyu; Cao, Tingting; Wu, Shuo; Zhu, Fenghui
Abstract : A simple and easy-operation electrode modification strategy was proposed using Cu-MOF/GO nanohybrids for physiologists and pathologists for the feasible and reliable simultaneous electrochemical detections of DNA bases, namely guanine and adenine. Abstract : A simple and easy-operation electrode modification strategy was proposed using Cu-MOF/GO nanohybrids for physiologists and pathologists for the feasible and reliable simultaneous electrochemical detections of DNA bases, namely guanine and adenine. The nanohybrids were prepared via a simple ultrasonic method and were employed for the fabrication of a sensing interface. SEM, TEM, XRD, FT-IR, and electrochemical characterizations were used to characterize the general morphology and structure of the nonohybrids. The proposed Cu-MOF/ERGO/GCE exhibited ultra-stable and high-sensitivity performance in the simultaneous electrochemical detection of guanine and adenine. The recorded DPV curves revealed a linear increase in the faradaic signals with increase in the concentrations of guanine and adenine in the range of 0.02–10 µM and 20–100 µM for guanine, and 0.005–20 µM and 40–200 µM for adenine. The relative standard deviation of guanine and adenine for 50 consecutive detections is 1.37% and 1.92%, respectively. It was proved that the proposed Cu-MOF/ERGO/GCE can be performed for the detection of guanine and adenine in real samples, such as Herring sperm DNA, and satisfactory results were obtained. This strategy does not require complicated modification procedures, professional modification techniques, or sophisticated instruments, but it can provide a highly sensitive and stable detection method, which is expected to expand and deepen the applications of electrochemical detection in life science research.